Respuesta :

[tex]\frac { 2 }{ 3 } \left( x-4 \right) =2x\\ \\ 3\cdot \frac { 2 }{ 3 } \left( x-4 \right) =3\cdot 2x\\ \\ 2\left( x-4 \right) =6x\\ \\ 2x-8=6x\\ \\ 6x-2x=-8\\ \\ 4x=-8\\ \\ x=-\frac { 8 }{ 4 } \\ \\ x=-2[/tex]
2/3 (x - 4 ) = 2x

Simplify both sides of the equation.

2/3(x−4)=2x

Simplify:

2/3(x−4)=2x

(2/3)(x)+(2/3)(−4)=2x(Distribute)

2/3x+−8/3=2x

Subtract 2x from both sides.

2/3x+−8/3−2x=2x−2x

−4/3x+−8/3=0

Add 8/3 to both sides.

−4/3x+−8/3+8/3=0+8/3

−4/3x=8/3

Multiply both sides by 3/(-4).

(3/−4)*(−4/3x)=(3/−4)*(8/3)

x=−2